COVID-19 safe and fully operational radiotherapy: An AIRO survey depicting the Italian landscape at the dawn of phase 2. (February 2021) - Jereczek-Fossa, Barbara Alicja; Pepa, Matteo; Zaffaroni, Mattia; Marvaso, Giulia; Bruni, Alessio; Buglione di Monale e Bastia, Michela; Catalano, Gianpiero; Filippi, Andrea Riccardo; Franco, Pierfrancesco; Gambacorta, Maria Antonietta; Genovesi, Domenico; Iatì, Giuseppe; et al.
Highlights: Italy has been slowly reopening after a 10 week lockdown following COVID-19 outbreak. A survey was administered to Italian RT departments to depict the current scenario. In P1, RT departments managed to contain contagion with modest workload reduction. All safety measures, maintained in P2, allowed RT departments to restore activities. Reorganization of activities will be crucial to prevent the second wave of pandemic.